Digital Solutions for Islamic Charity: The Impact of Cryptocurrency on Zakat, Infaq, and Sadaqah - Pranata, Eka Octavian; Nabilah, Deva; Ma’rifah, Aula Nurul (LP2M IAIN Palopo, 2025)
In the digital age, financial technology (fintech) developments offer new opportunities for the practice of Islamic charity, particularly zakat, infaq, and sadaqah (ZIS). One of the most innovative solutions is the use of cryptocurrency in these charitable activities. This article aims to analyze the impact of cryptocurrency adoption in the collection and distribution of ZIS by reviewing relevant literature and existing case studies. The research seeks to understand the potential, challenges, and legal implications of utilizing cryptocurrency in Islamic charity. The findings reveal that while cryptocurrency has the potential to enhance the efficiency and transparency of ZIS collection, it also presents challenges related to regulation, value stability, and acceptance by religious authorities.